Teacher perception about gender equality and the hidden curriculum - Moya-Díaz, Ignacio; De-Juanas, Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research aimed to analyze the perception of teachers in the gender equality construct. For its development, an ex post facto quantitative study was designed using the Hidden Gender Equality Scale. It was applied to an incidental sample of 391 teachers from the Community of Madrid. For data analysis, the following tests were applied: Student’s t, ANOVA and MANOVA. The results revealed significant differences in the main dimensions of the IGOE scale. The Gender Situation at School dimension acted as the main transmitter of sexist stereotypes, attitudes and, behaviors through the hidden curriculum.